(untitled) (BIOM - Revue scientifique pour la biodiversité du Massif central, 2022)
The Poix spring is a geological particularity of the French Massif central as it is known to be bitumen associated with salt water, methane and traces of hydrogen sulphide. Between March 2017 and June 2020, three samples were taken by scraping the diatoms on the layer of bitumen. Moreover, the physical and chemical conditions were examined. It appears that the conductivity of the saline water is higher than the one of the ocean leading to the development of some brackish diatom species observed for some of them on the intertidal sediments or estuaries. Even if the abiotic conditions were extreme for these algae, the biodiversity was high and reveals species with high ability to withstand in high salinity concentrations and fluctuations.